Effectiveness of intravitreal ranibizumab for diabetic macular edema in vitrectomized versus non-vitrectomized eyes: a Meta-analysis - Yi-Heng Wang; Qian Xu; Jie Luan (International Journal of Ophthalmology, 2024)
AIM: To evaluate the effectiveness and safety of intravitreal ranibizumab (IVR) for diabetic macular edema (DME) in vitrectomized versus non-vitrectomized eyes. METHODS: The PubMed, EMBASE, Web of Science, Cochrane, EBSCO were comprehensively searched for studies comparing vitrectomized and non-vitrectomized eyes with DME. Clinical outcomes of best-corrected visual acuity (BCVA), central macular thickness (CMT), the mean number of intravitreal injection and adverse events were extracted and analyzed. RESULTS: Six studies involving 641 eyes were included. Final visual gain significantly improved and CMT significantly reduced in vitrectomized eyes at 6mo and 12mo visits (P<0.05). Although the mean reduction in CMT among non-vitrectomized eyes was significantly greater than in vitrectomized eyes at the 6mo [mean difference (MD)=53.57, 95% confidence interval (CI): 28.03 to 78.72, P<0.0001] and 12mo (MD=49.65, 95%CI: 19.58 to 79.72, P=0.01), no significant difference was detected in improvement in BCVA at either 6mo (MD=0.05, 95%CI: -0.02 to 0.13, P=0.14) or 12mo (MD=0.03, 95%CI: -0.04 to 0.09, P=0.43). Injection number of ranibizumab in non-vitrectomized eyes was significantly less than that in vitrectomized eyes during 6-month period (MD=0.60, 95%CI: 0.16 to 1.04, P=0.008), while there was no statistically significant difference between the two groups during 12mo of follow-up. CONCLUSION: Evidence from current study suggests that IVR was useful for both vitrectomized group and non-vitrectomized group with DME. Although less reduction in macular thickness is found in vitrectomized group, visual improvement between two groups is similar.